Remarks at the Global Health Summit Co-Hosted by the European Commission and Italy - Malpass, David (World Bank, Washington, DC, 2021)
World Bank Group President David Malpass highlighted that in the first year of the pandemic, the World Bank Group committed $180 billion to help countries respond to the health, economic, and social impacts of the pandemic. The Bank authorized $12 billion to help countries access and deploy vaccines, with the goal of vaccinating a billion people in developing countries. The World Bank launched a website to make all information about our vaccination projects easily accessible in one place. He urged countries with excess supplies to release their surplus doses as soon as possible to developing countries that have vaccination operations already in place, and he also urged all of them to increase the transparency of these delivery commitments. At Tuesday’s Summit on Financing of African Economies, he announced his commitment to provide $150 billion in financing for sub-Saharan Africa over the next five years. Pandemic preparedness means investments across sectors, not just in health. The Coronavirus (COVID-19) pandemic has shown that social safety nets that provide digital cash transfers are particularly valuable, adding to the resilience of food security, basic health, and education. He concluded that the World Bank Group is committed to the health agenda. By working together, we can help developing countries build the resilience they need when they face major threats to their people’s health.